Outcome of therapy in biopsy proven lupus nephritis with cyclophosphamide or mycophenolate: Registry data from a South Indian tertiary care center - Keerthi Talari; Rajendra Varaprasad Irlapati; Megha Uppin; Liza Rajasekhar (Indian Journal of Rheumatology)
Background: Cyclophosphamide and mycophenolate are the currently proposed first-line agents for induction in lupus nephritis (LN). In this study, we analysed the response rates with the three different induction regimens currently available for LN. Methods: Patients with biopsy-proven LN with data available at least till completion of induction regimen was included. Data on demography, clinical, laboratory measures, disease activity, and treatment received at baseline, at the end of induction, and until the last follow-up were retrieved. Response at the end of induction was noted. Differences between groups were analyzed using Chi-square test. Results: Eighty-three patients (75 females) with the mean age of 25 ± 8.9 years were included. The median duration of follow-up was 18 months (range: 6–153). Forty-one patients had Class IV, 19 Class III, 11 Class V, 7 Class III/IV + V, and 5 Class II LN. Forty received high-dose cyclophosphamide (HD CyC), 14 Euro-Lupus Nephritis Trial cyclophosphamide (ELNT CyC), 20 mycophenolate mofetil (MMF) for induction, while two received azathioprine, one cyclosporine, one modified ponticelli, and five with Class II nephritis received no induction. Baseline characteristics were comparable between three groups. The response rate was similar between the three groups: 30/40 in the HD CyC group, 12/14 in the ELNT CyC group, and 15/20 in the MMF group responded at the end of induction (P = 0.69). Complete response rate was higher in the individuals who received cyclophosphamide (HD CyC + ELNT CyC) as compared to MMF (17/34 vs. 2/13, P = 0.05). Univariate analysis of factors predicting response revealed only class of nephritis as a significant factor predicting response (complete or partial) at the end of induction therapy. Conclusion: In this South Indian lupus registry a complete response at 6 months in biopsy-proven LN was better with cyclophosphamide than mycophenolate.